Organometallic‐Mediated Alternating Radical Copolymerization of tert‐Butyl‐2‐Trifluoromethacrylate with Vinyl Acetate and Synthesis of Block Copolymers Thereof. Issue 15 (31st May 2017) - Banerjee, Sanjib; Ladmiral, Vincent; Debuigne, Antoine; Detrembleur, Christophe; Rahaman, S. M. Wahidur; Poli, Rinaldo; Ameduri, Bruno
Abstract : Organometallic‐mediated radical copolymerization is successfully employed for 1:1 alternating controlled copolymerization (independent of the monomer feed) of VAc (electron‐donating) and MAF‐TBE (electron‐accepting). By simply tuning the comonomer feed ratio, well‐defined poly(VAc‐ alt ‐MAF‐TBE) alternating copolymers or novel poly(VAc‐ alt ‐MAF‐TBE)‐ b ‐PVAc diblock copolymers (comprising one alternating block and one homopolymer block) can be prepared. Abstract : Organometallic‐mediated radical polymerization (OMRP) has given access to well‐defined poly(vinyl acetate‐ alt ‐tert‐butyl‐2‐trifluoromethacrylate)‐ b ‐poly(vinyl acetate) and poly(VAc‐ alt ‐MAF‐TBE) copolymers composed of two electronically distinct monomers: vinyl acetate (VAc, donor, D) and tert ‐butyl‐2‐trifluoromethacrylate (MAF‐TBE, acceptor, A), with low dispersity (≤1.24) and molar masses up to 57 000 g mol −1 . These copolymers have a precise 1:1 alternating structure over a wide range of comonomer feed compositions. The reactivity ratios are determined as r VAc = 0.01 ± 0.01 and r MAF‐TBE = 0 at 40 °C. Remarkably, from a feed containing >50% molar VAc content, poly(VAc‐ alt ‐MAF‐TBE)‐ b ‐PVAc block copolymers are produced via a one‐pot synthesis. Such diblock copolymers exhibit two glass transition temperatures attributed to the alternating and homopolymer sequences. The OMRP of this fluorine‐containing alternating monomer system may provide access to a wide range of new polymer materials.